AMBIGUITAS STRATEGI IDENTITAS CNN TERHADAP ISLAMOPHOBIA DAN ANTI-AMERIKA (KASUS: CNN.COM DAN CNNINDONESIA.COM) - Sabda Ningsih (Indonesian Journal of International Relations, 2022)
This study analyzes the constructivist view of CNN's strategy on Islamophobia and Anti-American issues. Taking a case study of Islamophobia globally and Anti-Americanism in Indonesia, CNN provides two different identities regarding each issue that contradicts the assumptions of constructivism. Through descriptive qualitative research techniques and data collection documentation, the authors found that the strategy with two different identities for Islamophobia and Anti-Americanism is CNN's effort as a framing for the interests of the United States in the war on terror, as well as differentiating them from other news media. With news characteristics that are skeptical of the Middle East, CNN provides an identity as a supporter of Islamophobia and encourages the movement to grow. It's different if you switch to Indonesian news, CNN abandons its previous identity and builds a new identity with a narrative that supports Muslims from the point of view of Western countries. For constructivism, this dual identity strategy shows that CNN is a weak actor because they do not know who they really are and the ambiguity of the main interests they want to achieve